THE INFLUENCE OF INTERPERSONAL COMMUNICATION AND WORK ETHIC ON EMPLOYEE PERFORMANCE WITH COMMITMENT AS A MODERATING VARIABLE - Barham Siregar; Evada Rustina; Normansyah Normansyah; Roosganda Elizabeth; Muhammad Halfi Indra Syahputra (JURNAL ILMIAH EDUNOMIKA, 2024)
Employee performance is the most fundamental factor in improving company performance. There are a number of factors that can influence employee performance in a company, including good internal communication and a work ethic that continues to improve among employees. Therefore, this research aims to examine the influence of interpersonal communication and work ethic on employee performance. Different from previous research, this research adds the Commitment variable as a moderating variable. This research is quantitative research, namely research that serves as a stepping stone for previous research to find new variations in this research. This research uses secondary data which is distributed through questionnaires. The data used was analyzed using smart PLS 3.0. The research results show that the Interpersonal Communication and Work Ethic variables have a positive relationship and have a significant influence. In line with the researchers' assumptions, the Commitment variable can moderate the influence of Interpersonal Communication and Work Ethic on Employee Performance. Keywords : Interpersonal Communation, Work Etic, Commitment, Employee Peforamnce..